Is the term "anti-anaerobic" still relevant?. (January 2021) - Woerther, Paul-Louis; d'Humières, Camille; Lescure, Xavier; Dubreuil, Luc; Rodriguez, Christophe; Barbier, François; Fihman, Vincent; Ruppé, Etienne
Highlights: "Anti-anaerobic" antibiotics are premised on equivalent resistance profiles of anaerobic bacteria. Many antibiotics, although not "anti-anaerobic", can be effective on infections by anaerobes. Effect of antibiotics on intestinal microbiota is poorly related to "anti-anaerobic" spectrum. Current knowledge does not support the concept of the "anti-anaerobic" spectrum. Next-generation sequencing is expected to improve the treatment of anaerobic infections. Abstract: For decades, the term "anti-anaerobic" has been commonly used to refer to antibiotics exhibiting activity against anaerobic bacteria, also designated as anaerobes. This term is used in various situations ranging from infections associated with well-identified pathogens like Clostridioides difficile, or Fusobacterium necrophorum in Lemierre's syndrome, that require specific antibiotic treatments to polymicrobial infections generally resulting from the decreased permeability of anatomical barriers (e.g., intestinal translocation and stercoral peritonitis) or infectious secondary localizations (e.g., brain abscess and infectious pleurisy). In these cases, the causal bacteria generally remain unidentified and the antimicrobial treatment is empirical. However, major progress in the knowledge of human bacterial microbiotas in the last 10 years has shown how diverse are the species involved in these communities. Here, we sought to reappraise the concept of anti-anaerobic spectrum in the light of recent advances in the microbiota field. We first highlight that the term anaerobic itself does not represent the tremendous diversity of the bacteria it spans, and then we stress that the antibiotic susceptibility profiles for most anaerobic bacteria remain unaddressed. Furthermore, we provide examples challenging the relevance of the "anti-anaerobic" spectrum from a clinical and ecological perspective.